2003
DOI: 10.4049/jimmunol.170.2.1052
|View full text |Cite
|
Sign up to set email alerts
|

CpG DNA Induces Self and Cross-Hyporesponsiveness of RAW264.7 Cells in Response to CpG DNA and Lipopolysaccharide: Alterations in IL-1 Receptor-Associated Kinase Expression

Abstract: Exposure of macrophages to LPS induces a state of hyporesponsiveness to subsequent challenge with LPS. It has not been known whether previous exposure to CpG DNA induces a similar suppressive response to subsequent stimulation with CpG DNA. In the present study, we demonstrate that pretreatment with CpG DNA induces suppression of cytokine release in a murine macrophage-like cell RAW264.7 in response to subsequent challenge by CpG DNA. Additionally, CpG DNA-mediated activation of mitogen-activated protein kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
110
4
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 63 publications
8
110
4
2
Order By: Relevance
“…Hemozoin pigment is a ligand for TLR9 (26) and repeated stimulation through TLR9 can cause tolerance to signaling through TLR4 (27). We hypothesize that repeated signaling through TLR9 by hemozoin and other protozoan-derived ligands tolerizes or shunts the common MyD88 TLR signaling pathway such that anti-inflammatory cytokines are preferentially produced, resulting in the refractory state we and others (28) have observed.…”
Section: Late-stage Malaria Infection Results In Endotoxin Tolerance mentioning
confidence: 96%
“…Hemozoin pigment is a ligand for TLR9 (26) and repeated stimulation through TLR9 can cause tolerance to signaling through TLR4 (27). We hypothesize that repeated signaling through TLR9 by hemozoin and other protozoan-derived ligands tolerizes or shunts the common MyD88 TLR signaling pathway such that anti-inflammatory cytokines are preferentially produced, resulting in the refractory state we and others (28) have observed.…”
Section: Late-stage Malaria Infection Results In Endotoxin Tolerance mentioning
confidence: 96%
“…The conspicuous inhibition of TLR4-responsive signaling by ⌬FADD suggests reinforced mobilization of FADD by TLR4, which appears to be important for the activation of apoptosis in our experimental conditions. It has been shown that TLR4 but not TLR2 activation results in degradation of the IRAK1 molecule (68,69). Binding of IRAK1 to the MyD88 death domain is an important step of the TLR-responsive signal relay that leads to NF-B activation (1)(2)(3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…34 Of special interest is the finding that interleukin-1 receptor associated kinase (IRAK) 18 -1 is altered at least in some aspects of TLR signalling 19 , a result that has been confirmed by different groups. 16,20,34 Without claiming completeness for the various findings of tolerance experiments, it has to be stated that different modes of action seem to be operative and that TLR ligands seem to make different use of them.…”
Section: Discussionmentioning
confidence: 99%